Exploring the composition of the Pentateuch - Baker, Leslie Scott, Jr; Bergland, Kenneth; Masotti, Felipe A.; Wells, A. Rahel (Abigail Rahel) (Bulletin for biblical research supplements, 2020)
"A collection of revised papers from a 2016 conference at Andrews University, exploring new ideas about the composition of the Pentateuch that arise from analysis of the biblical text"--